Answer:
Explanation:
The given expression is:
[tex]\frac{2m^2+m-15}{m^2-9}[/tex]
The numerator can be siplified by using factorization and denominator will be simplified using the formula
[tex]a^2-b^2 = (a+b)(a-b)[/tex]
So,
[tex]= \frac{2m^2+6m-5m-15}{(m)^2-(3)^2}\\=\frac{2m(m+3)-5(m+3)}{(m-3)(m+3)}\\=\frac{(2m-5)(m+3)}{(m-3)(m+3)}\\=\frac{2m-5}{m-3}[/tex]
A fraction is undefined when the denominator is zero. In order to find the value of m on which the simplified fraction will be undefined we will put denominator equal to zero.
So,
[tex]m-3 = 0 => m = 3[/tex]
Hence,